Kesiapan Mahasiswa Mengikuti Pembelajaran Daring di Masa Pandemi Covid-19 - Aditya Chandra Setiawan (Faculty of Education Universitas Negeri Malang, 2021)
Abstract: This study describes the factors of readiness of students to follow online learning during the covid-19 pandemic; and discover the factors that formed about the readiness of students to follow online learning during the covid-19 pandemic. The research method used is quantitative-explorative approach with EFA (Exploratory Factor Analysis) model and factor analysis assumption test. The respondents to the study were students of the Faculty of Education, State University of Surabaya as of the 2019/2020 school year a total of 4,244 respondents. Sampling using sampling techniques is simple random sampling, quota sampling and a total of 221 respondents. This study concluded that there are 20 (twenty) indicator items identified based on the results of previous research and found 6 (six) factors of student readiness to follow online learning during the covid-19 pandemic formed from indicators. Abstrak: Penelitian ini mendeskripsikan faktor kesiapan mahasiswa mengikuti pembelajaran daring pada masa pandemi covid-19; dan menemukan faktor yang terbentuk tentang kesiapan mahasiswa mengikuti pembelajaran daring di masa pandemi covid-19. Metode penelitian yang digunakan adalah pendekatan kuantitatif-eksploratif dengan model EFA (Exploratory Factor Analysis) dan uji asumsi analisis faktor. Responden penelitian adalah mahasiswa Fakultas Ilmu Pendidikan, Universitas Negeri Surabaya per tahun ajaran 2019/2020 sejumlah 4.244 responden. Pengambilan sampel menggunakan teknik sampling yaitu simple random sampling, quota sampling dan sejumlah 221 responden. Penelitian ini menyimpulkan bahwa terdapat 20 (dua puluh) butir indikator yang diidentifikasi berdasarkan hasil penelitian terdahulu dan menemukan 6 (enam) faktor kesiapan mahasiswa mengikuti pembelajaran daring pada masa pandemi covid-19 yang terbentuk dari indikator-indikator.